2011
DOI: 10.5114/aoms.2011.20608
|View full text |Cite
|
Sign up to set email alerts
|

Is there a relationship between admission blood glucose level following acute poisoning and clinical outcome?

Abstract: IntroductionThe aim of this study was to investigate the relationship between the admission blood glucose level following acute poisoning, severity of acute poisoning and clinical outcome.Material and methodsThis prospective study was conducted on 345 deliberate self-poisoning patients. Standard demographic and clinical information; admission blood glucose level; poisoning severity score and outcome were recorded. Patients with a history of diabetes mellitus, receipt of pre-sampling intravenous dextrose soluti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
20
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 31 publications
1
20
0
1
Order By: Relevance
“…[36] The association between glucose levels and mortality in patients with organophosphate and methanol poisoning has been proven. [37,38] We did not include glucose levels in the nomogram, based on the results of multivariate analysis.…”
Section: Discussionmentioning
confidence: 99%
“…[36] The association between glucose levels and mortality in patients with organophosphate and methanol poisoning has been proven. [37,38] We did not include glucose levels in the nomogram, based on the results of multivariate analysis.…”
Section: Discussionmentioning
confidence: 99%
“…The type of drug determines whether hyper-or hypo-glycemia occurs (Sabzghabaee et al 2011;Pohanka, Románek, and Pikula 2012). Long-term hyperglycemia may be involved in many life-threatening complications such as cardiovascular diseases, diabetic nephropathy, neuropathy, and rethinopathy.…”
Section: Introductionmentioning
confidence: 99%
“…It is critical to quantify the medical severity of SBSP in suicide attempt cases. First, accurate assessment of the medical severity of SBSP informs medical treatment, including guiding decisions about admission, level of care, and length of stay (Cevik, Unluoglu, Yanturali, Kalkan, & Sahin, 2006;Sabzghabaee, Eizadi-Mood, Gheshlaghi, Adib, & Safaeian, 2011). Second, patients who make more medically severe suicide attempts are at higher risk for eventual suicide than those who make suicide attempts of lower medical severity (Beautrais, 2004;Hawton & Fagg, 1988;Ostamo & Lonnqvist, 2001), underscoring the importance of vigilance with these patients.…”
mentioning
confidence: 99%
“…Importantly, because it takes into consideration all major organ systems in scoring, it is capable of assessing a broad range of poisoning effects, making it optimal for widespread use including in medico-legal cases. Following its introduction and initial testing, evidence for the validity of the PSS has been based on studies of calls to Poison Centers (Bentur, Raikhlin-Eisenkraft, & Lavee, 2004;Casey, Dexter, Michell, & Vale, 1998;Wong, Taylor, Ashby, & Robinson, 2010) and poisoning patients presenting to hospital (Peter et al, 2013;Sabzghabaee et al, 2011;Thanacoody et al, 2016). This research has shown that the PSS predicts clinical outcomes including mortality (Peter et al, 2013;Sabzghabaee et al, 2011;Thanacoody et al, 2016) and that it is correlated with other validated measures of acute medical morbidity (Akdur et al, 2010;Churi, Ramesh, Bhakta, & Chris, 2012;Peter et al, 2013;Sam et al, 2009).…”
mentioning
confidence: 99%
See 1 more Smart Citation